The soldiers needed to be awakened: Tumor-infiltrating immune cells - Yaping, Wang; Zhe, Wang; Zhuling, Chu; Ruolei, Li; Pengyu, Fan; Lili, Guo; Cheng, Ji; Bo, Zhang; Liuyin, Liu; Guangdong, Hou; Yaoling, Wang; Niuniu, Hou; et al. (Frontiers in Genetics, 2022)
In the tumor microenvironment, tumor-infiltrating immune cells (TIICs) are a key component. Different types of TIICs play distinct roles. CD8+T cells and natural killer (NK) cells could secret soluble factors to hinder tumor cell growth, whereas regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) release inhibitory factors to promote tumor growth and progression. In the meantime, a growing body of evidence illustrates that the balance between pro- and anti-tumor responses of TIICs is associated with the prognosis in the tumor microenvironment. Therefore, in order to boost anti-tumor response and improve the clinical outcome of tumor patients, a variety of anti-tumor strategies for targeting TIICs based on their respective functions have been developed and obtained good treatment benefits, including mainly immune checkpoint blockade (ICB), adoptive cell therapies (ACT), Chimeric antigen receptor (CAR) T cells and various monoclonal antibodies. In recent years, the tumor-specific features of immune cells are further investigated by various methods like using single-cell RNA sequencing (scRNA-seq) and the results indicate that these cells have diverse phenotypes in different types of tumors and emerge inconsistent therapeutic responses. Hence, we concluded the recent advances in tumor-infiltrating immune cells, including functions, prognostic values, and various immunotherapy strategies for each immune cell in different tumors.